Using virtual environments to study health related decisions: early results using a new effort task. - Thomas, Stephanie; Xie, Feng; Buckley, Neil; Cameron, David; Cuff, Katherine; Feeny, David; Hurley, Jeremiah; Mestelman, Stuart (2019)
This project investigates the viability of using virtual world environments for controlled laboratory investigations of health preferences and behaviours. We will observe whether participants exhibit a willingness to pay to avoid a reduction in their mobility in the virtual world. The key aim is to understand if a virtual world can provide sufficient context to prompt participants to make health related decisions and to learn more about the use of such environments.